Experimental study on the scrubbing efficiency of aerosols contained in horizontal and vertically downward submerged gas jet. (August 2020) - Diao, Han; Zhou, Yanmin; Gu, Haifeng; Li, Yingzhi; Yan, Chaoxing
Abstract: The scrubbing efficiency of aerosols contained in submerged gas jet in Pressure Suppression Pool (PSP) is important during the severe accident of Nuclear Power Plant (NPP). To analyze the influence of nozzle inlet pressure (from 0.12 MPa to 0.4 MPa) and gas injection direction (horizontal and vertically downward direction) on scrubbing efficiency of aerosols in non-condensable gas submerged jet, several experiments were carried out. The experimental results show that the aerosol scrubbing efficiency increases as the inlet pressure increases. Most of the aerosols in gas are retained in water when the nozzle inlet pressure is higher than 0.2 MPa, and the scrubbing efficiency is lower than 90% under low inlet pressure. The effect of gas injection direction on scrubbing efficiency is significant when the gas flow state at nozzle exit is subcritical flow, but the effect is not obvious when the inlet pressure is higher than 0.3 MPa and the gas flow state at nozzle exit is critical flow. Highlights: The scrubbing efficiency of aerosols in horizontal submerged jet increases as the nozzle inlet pressure increases. The scrubbing efficiency of aerosols in vertically downward submerged jet increases as the inlet pressure increases. The gas injection velocity is the key factor to affect the scrubbing efficiency of aerosols in non-condensable gas submerged jet.